Knowledge, attitude and determinants of post-abortion contraceptive use among women of reproductive age seeking care in healthcare facilities in Ile-Ife, Nigeria: a cross-sectional study - Uchechi Grace Okonta; Olabisi Muslimat Odekunle (BMJ Public Health)
Background Post-abortion contraception is the commencement of the chosen contraception method immediately after or within 48 hours of an abortion episode. It is a key strategy for the reduction of unintended pregnancies and repeated abortion.Objective The study aimed to assess the knowledge and attitude towards post-abortion contraception and examine the determinants of post-abortion contraceptive use among women of reproductive age seeking care in healthcare facilities in Ile-Ife.Design The study was a facility-based descriptive cross-sectional survey which employed a quantitative method.Method The study was conducted among women of reproductive age who have had abortion and are seeking care in the family planning units of healthcare facilities in Ile- Ife. 285 respondents were recruited for the study using a two-stage sampling technique. A pre-tested interviewer-administered structured questionnaire was used for data collection. Data was analysed using IBM Statistical Product for Service Solutions (SPSS) version 23. Three levels of analyses were carried out—univariate, bivariate and multivariate—to determine the frequencies of variables and summary statistics, the association between awareness and knowledge of post-abortion contraception, attitude as well as post-abortion contraceptive use and to identify factors influencing post-abortion contraception use. The level of significance was determined at a p value of less than 0.05.Results 53% had adequate knowledge of post-abortion contraception. 22% of the women had used or accepted the use of post-abortion contraceptives. The factors influencing post-abortion contraception use were educational status, socio-economic status, number of pregnancies and number of living children. The study concluded that post-abortion contraception use was low among women of reproductive age seeking abortion services.Conclusion The study concluded that post-abortion contraceptive use was low among women of reproductive age seeking abortion services. There is a need for increased knowledge of the importance of post-abortion contraception through community awareness and mass media. Further research on follow-up discontinuation rates of post-abortion contraception use should be investigated.